Quidam magnus videlicet vir et sapiens. Rhetoric and Philosophy in Cicero’s De inventione - Delle Donne, Carlo (Ciceroniana On Line, 2024)
The article analyzes the prologue of the first book of Cicero’s De inventione, focusing on the deep thematic unity that connects the prologue with the rest of the text. It also examines the figure of the sage who, according to Cicero, facilitated the emergence of civilization. The article highlights the philosophical stature of this figure and traces in it a subtle critique of the Epicurean conception of language, as reconstructed from Lucretius’ De rerum natura V.